Oral health education program and competencies among nurses whose recipients are totally dependent patients - Ragotero, Ina Gonzales- (Thesis -- (Master of Arts in Nursing) -- University of the Philippines Manila.)
The outcome for competence in oral care has consistently been emphasized to improve oral care practices. However, several factors have been observed to effect the quality of oral care practice of nurses for patient who are totally dependent in terms of activities of daily living. Circumstances surrounding hospitalization and ill-health can lead to neglect of oral hygiene. Long-term hospitalization makes patients vulnerable and susceptible to bacterial and other infections that would compromised their health and chance for recovery. Nursing intervention such as oral hygiene help prevent complications, such as infection. Studies have linked oral pathogens to hospital-acquired infections. These studies indicate that oral hygiene is an integral to prevention of infection among hospitalized patients. While a lot of studies about oral care and the knowledge level has been done, there is dearth of study in the area of skills and attitude.
The study aimed to determine four objectives: (1) To determine the competency level of nurses on oral care practices (outcome variables/dependent) in terms of knowledge, skills and attitude before the oral health educational program (OHEP) (independent variable). (2) To determine whether there is a difference (change) in competency level of nurses on oral care practice in terms of knowledge, skills, and attitude, after the oral care educational program. (3) To determine if the following variables are associated with competency level of nurses on oral care (knowledge, skills, and attitude): Age, Length of work experience, Education and training, Oral care involvement. (4) To describe the experiences of nurses on oral care practices whose recipients of oral care are totally dependent patients in terms of activities of daily living.
The quasi-experimental one group pre-post test design was used. The study was conducted at the Armed Forces of the Philippines General Hospital (AFPGH) and Philippine General Hospital (PGH). The subjects were Intensive Care Unit nurses assigned in the clinical areas where patients are totally dependent on nurses in terms of activity of daily living. The study utilized pre and post test for comparison purposes. Sixty-six nurses participated in the study. Thirty-eight (38) nurses in PGH and twenty-eight (28) in AFPGH. The subjects were all subjected to pre and post exposure to the oral health education program intervention. All subjects took the pre-test and post-test.
The Oral Health Education Program is structured, following the essentials for a competency-based program. The OHEP seminar workshop session includes the topics on Anatomy and Physiology of the oral cavity, Assessment and Documentation, Oral Care intervention, Oral Pathology, and Evidence based oral care practices. These topics focus on the survival knowledge and skills to address the priority learning needs of ICU nurses in regards to oral care practices for totally dependent patients. There were sets of scheduled sessions provided to train the nurses. Each session lasted for about an hour and half. The instruments used were Nurse Profile, Oral health Knowledge Test, Oral Health Skills Test and the Oral Health Attitude Scale Test.
To provide the general profile of the nurse respondents, descriptive statistics was used. Test statistic Wilcoxon test and Spearman Rho were utilized in the analysis of data. The study yielded the following results
There was a difference in the competency level between the pretest and post-test group in each of the components (knowledge, skills and attitude) and in the overall z value, p>.05) using Wilcoxon test. Nurses in the Post test group had higher competency scores.
Nurse who attended the Oral Health Educational Program (OHEP) significantly improved their competency based on Wilxcoxon test (z=, p value .0000) in terms of knowledge, skills and attitude. All nurse factors were not related to the overall competency of nurses in oral care. However, having oral care training or workshop in oral care had a slight relationship to knowledge (rs. 249 p>.05).
The Oral Health Education Program helped improve the competency level of nurses on oral care practice. Oral training program is associated with increase in knowledge on oral care practice.
Suggested recommendations are as follows: 1) The Oral Health Educational Program (OHEP). It is recommended that the OHEP to be utilized for skill development in oral care assessment and intervention of nurses. 2)A more comprehensive oral care training program involving other areas in oral health care can be developed. This will help integrate patient education in the nursing role and can be integrated in the undergrad nursing curriculum as part of the evidence based practice. 3) The use of oral kits as an equipment for oral care is highly recommended due to its capability for better oral care practice and ease of use. 4)It is also recommended that a replication study be used with a larger sample. 5) To upgrade oral care competency in the basic Nursing curriculum. 6) To consider the role of the dentist as part of the hospital health team. 7) The use of oral kits as an equipment for oral care is highly recommended due to its capability for better oral care practice and ease of use. 8) It is also recommended that a replication study be used with a larger sample.
The program on oral care training is useful in training all nurses of the institution on oral care practice like assessment, monitoring, documentation and intervention. This serves as an introductory program for a more comprehensive training of nurses in oral care. The skills development as a component of training is an important feature. The study increases awareness of nursing administration on the need for quality. The findings of the study show that Standardized Oral Health Educational Program for nurses can be a valuable tool in health promotion, education, research, practice enhancement and eventually early identification of oral pathology.
Keywords: Oral Health Education Program; Competency-Based Education